Ostrich-like strategies in Sahelian sands?: land and water grabbing in the Office du Niger, Mali - Hertzog, T.; Adamczewski, A.; Molle, Francois; Poussin, Jean-Christophe; Jamin, Jean-Yves (2012)
In recent years, large-scale agricultural investment projects have increased in sub-Saharan Africa as a result of the growing appetites of local and international investors for land resources. Research has so far mainly focused on land issues, but the water implications of these land deals are starting to surface. Taking the Office du Niger (ON), in Mali, as a case study, it is shown that while around 100,000 ha is currently being cultivated, mostly by smallholders, a total of 600,000 ha of land has been allocated in the past ten years to investors in large-scale farming. This process has largely bypassed the official procedure established by the ON at regional level. The allocation of new lands has shifted to the national level, with an attempt to recentralize the management of land deals and associated benefits at the highest level, despite contrary efforts by foreign donors to strengthen the ON. This article describes the complex allocation process based on 'behind-closed-doors' negotiations. It then analyses the implications of the land deals on water issues by focusing on the strategies of actors to limit the risk of future water shortages, the current and expected difficulties in water management and allocation, and the emerging spatial and social redistribution of benefits and risk that signals a process of water grabbing.